AvaII senses m6A and inosine sites and enables targeted nanopore direct RNA-sequencing - Naarmann-De Vries, Isabel S.; Preissendörfer, Tim; König, Julian; Dieterich, Christoph (Frontiers in Molecular Biosciences, 2025)
Nanopore direct RNA-sequencing is the first commercialized method to sequence native RNA directly, thus preserving RNA modifications. With the current technology, sequencing is initiated from the 3′end. While for relatively short polyadenylated RNAs, full coverage is obtained, the 5′end of many long RNAs is not sufficiently covered resulting in a substantial 3′bias. We aimed to cleave such RNAs in a sequence-specific manner in order to generate new unique 3′ends that can be targeted by custom adapters. We identified the DNA endonuclease AvaII as a candidate enzyme. AvaII was originally described to cleave double-stranded DNA at GGWCC sites, where W is an A or T. Here, we show that AvaII cleaves also long RNAs in GGACC contexts, if hybridized to a complementary DNA oligo. Furthermore, we provide evidence that AvaII cleavage of RNA is modification sensitive and does not cleave RNA with m6A or inosine in the central position. We propose AvaII as “methylation sensor” for the bona fide DRACH recognition motif GGACC of the m6A writer complex. Finally, we show that AvaII cleavage products are accessible to targeted Nanopore direct RNA-sequencing.